The model for evaluation of motor activity of schoolchildren - Павлова, Ю. О. (Physical Education Theory and Methodology, 2013)
The problems of development and implementation of methods for evaluation of children physical activity level were analyzed. The factors that have influence oт physical activity were analyzed and according data results the model for investigation of physical activity was developed. The components of this model were educational environment, demographic, social, psychological and medical factors. The complex methodic for evaluation of physical activity was constructed according to the proposed model. The 305 pupils of the sixth and eighth grades take part in investigation. 49% of eighth grade pupils and 57% of sixth grade pupils have medium level of physical activity. Boys had higher level of physical activity compared with girls. Generally among schoolgirls of eighth grade was in 8,4 times less person with high level of physical activity then in sixth grade. The developed technique can be used at research of health and healthy lifestyles of students and for evaluation of effectiveness of prevention programs.